Impact of invasive plant management on soil activity and litter decomposition in a tropical forest restoration - Parré, Fernando M.; Loiola, Priscilla P. [UNESP]; Ballarin, Caio S. [UNESP]; Monquero, Patrícia A. (Wiley, 2023)
Tropical forest restoration is needed to mitigate the negative consequences of anthropogenic disturbances and climate change. One of the main limitations for the establishment of tropical forests is the competition with invasive species decreasing the survival and growth of native trees. Invasion management should affect soil microorganisms, which play essential roles in nutrient cycling, plant nutrition and on ecosystem functioning. Although chemical and nonchemical methods are applied worldwide to herbaceous invasion management, their impacts on soil microbial biomass, respiration and litter decomposition have yet to be measured over longer timeframes (>3 months) after application. Using a 3-year-old tropical forest restoration managed through chemical (herbicide pulverization) or nonchemical (mowing) treatments, and a secondary native forest patch nearby used as reference, we measured (1) soil microbial biomass and (2) basal soil respiration over 6 months, and on (3) litter decomposition over 1 year, after one management. We used mixed models to test whether management affected the response variables and found that chemical management resulted in lower microbial biomass and respiration after 5 months. Similarly, after 1 year, litter decomposition rate under chemical management was lower than that in the nonchemical and in the control. Chemical management effects on soil activity and litter decomposition should be considered when choosing suitable methods and its frequency to manage invasion, targeting the success of native trees and general ecosystem functioning.
Keywords: alien species; herbicide; microbiota; monitoring; mowing; restoration